1993
DOI: 10.1159/000183770
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone and Diabetes mellitus

Abstract: The diabetogenic action of pituitary extracts containing growth hormone has been recognised for more than 60 years and the importance of growth hormone in the development and progression of diabetic retinopathy for more than 30 years. Hypophysectomy was the first effective treatment for retinopathy but was discontinued because of the risk of severe hypoglycaemia that it produced and the development of an alternative, less dangerous therapy -photocoagulation. The precise role and significance of growth hormone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Previous reports have indicated that insulin deficiency led to impaired hepatic IGF-I synthesis [27], and serum IGF-I levels were positively associated with the dose of insulin administration in type 1 DM patients [28]. Also, Sonksen’s group[29,30,31] have reported that insulin increased hepatic IGF-I expression and secretion. These data suggested that plasma insulin level was one of the positive regulators for serum IGF-I levels.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have indicated that insulin deficiency led to impaired hepatic IGF-I synthesis [27], and serum IGF-I levels were positively associated with the dose of insulin administration in type 1 DM patients [28]. Also, Sonksen’s group[29,30,31] have reported that insulin increased hepatic IGF-I expression and secretion. These data suggested that plasma insulin level was one of the positive regulators for serum IGF-I levels.…”
Section: Discussionmentioning
confidence: 99%
“…One paradox of the role of GH/IGF-1 in the genesis of on May 10, 2018 by guest http://mcb.asm.org/ microvascular complication of DM is that the liver is resistant to GH while GH action is required for the genesis of retinopathy and nephropathy (1,19,21,23,30). Tissue-specific differences in the expression of the GHR may play a role in this differential sensitivity of organs to the effects of DM (21).…”
Section: Discussionmentioning
confidence: 99%
“…For humans, acquired hypopituitarism ameliorated retinopathy and iatrogenic hypopituitarism was the standard care for proliferative retinopathy until the advent of laser coagulation therapy (24). In contrast there is resistance to GH's actions in promoting linear growth and IGF-1 generation in poorly controlled IDDM (30); animal and human studies indicate that decreased hepatic expression of GHR contributes to this resistance to GH's actions (1,19,21). However, the molecular mechanisms underlying the paradox of the liver becoming resistant but the kidney and retina retaining sensitivity to GH in DM is not known.…”
mentioning
confidence: 99%
“…Paradoxically, despite the increase in the concentrations of circulating GH in patients with poor glycemic control, the concentrations of circulating IGF-1 are decreased, suggesting a state of GH resistance/insensitivity in Type 1 DM [2426], Thus GH hypersecretion in Type 1 DM is the result of negative feedback on the hypothalamus and pituitary from reduced levels of circulating IGF-1 and decreased action of IGF-1 at the cellular level. The decrease in circulating levels of IGF-1 reflects a state of GH resistance secondary to decreased hepatic GHR mRNA and protein expression and abnormalities in GHR signaling pathways in the liver in uncontrolled diabetes.…”
Section: Gh/igf-1 Axis In Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…However, on continuing the administration of Samatuline the differences between treated and placebo group failed to maintain statistical significance. In patients with acromegaly, surgical ablation of pituitary adenoma resulted in decreased GH levels and GFR followed by decrease in kidney size to normal values [26]. …”
Section: Clinical Evidence For a Correlation Between Activity Of The mentioning
confidence: 99%